Effects Of Social Media Health Teaching Method On Self-Care Efficacy Of Post-Colostomy Patients - Xiangzhen, Ren; Ryan Ray, Gatbonton (Journal of Neonatal Surgery, 2025)
This quasi-experimental study investigated the effects of a social media-based health teaching intervention, specifically delivered via WeChat, on the self-care efficacy of post-colostomy patients in China. It was conducted at a tertiary hospital in Guangzhou and involved 62 patients who had undergone gastrointestinal surgery. The participants were divided equally into experimental and control groups, with the control group receiving standard pre-discharge education and telephone follow-ups and the experimental group participating in a one-month WeChat-based program offering multimedia self-care content, psychological support, and clinician interaction. Using the General Self-Efficacy Scale (GSES), pre- and post-intervention data revealed that the experimental group showed a statistically significant improvement in self-efficacy compared to the control group (mean score: 25.81 vs. 20.68). These findings show that targeted social media interventions can enhance patients’ confidence in managing their condition and may reduce post-surgical complications. The study also highlights the feasibility and cultural relevance of using WeChat as a platform for health education in Chinese clinical settings. Limitations include a short follow-up period and a non-random sample, suggesting the need for further longitudinal research.